Parameter study for the production of semi-crystalline polyetherimide particles via liquid-liquid phase separation and precipitation - Unger, Laura; Dechet, Maximilian; Fischer, S.; Schmidt, Jochen; Bück, Andreas (Procedia CIRP, 2022)
The production of micron-sized polymeric particles via liquid-liquid phase separation (LLPS) and precipitation was under investigation, as this study is a continuation of previous activities. Throughout the production process of LLPS, parameter variations were conducted in order to adjust the final product properties. These include the particle size distribution, the melting point, the specific melting enthalpy, the obtained particle shape and powder flowability properties. The herein adjusted parameters involve the polymer fraction in the solution, the rotation speed of the stirring unit and the cooling rate after dissolving the polymer-solvent mixture. The cooling rate and the polymer fraction defined both, the thermal and structural properties of the obtained semi-crystalline particles. A superior impact on the particle size distribution and morphology was obtained from the rotation speed of the stirring element. Thus, the resulting properties of precipitated microparticles can explicitly be controlled via the applied production parameters.
CRIS-Team Scopus Importer:2022-11-25
Keywords: High temperature thermoplast; Microparticles; Precipitation